Evaluation of Antidiabetic Prescriptions from Medical Reimbursement Applications at Banaras Hindu University Health Care Facility - Dev Priya; Suresh Purohit; B L Pandey; Shardendu Mishra (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Diabetes is on rapid increase in third world countries undergoing rapid transition in terms of development particularly in India, which is often being referred as Diabetic capital. It is a disease more prevalent at latter part of life of human beings when finances dwindle and social care gets neglected. The medication continues till the whole life on a regular basis. In present study, the objective has been to provide pharmacoeconomic medication to the diabetic pensioners in the backdrop as mentioned in above background. Methods: The data was collected at the medical reimbursement section of pensioners of the University. The data was examined to answer issues of therapeutic decisions in the light of the pharmacoeconomic considerations. In this paper essentially data on choice of prescriptions with the angle of pharmacoeconomic prudence were included. The dichotomy of specialist versus non specialist prescribers at the tertiary center (i.e. medical college hospital) was compared. Effort was made to define merit of the prescription based on comprehensive considerations of patient profile, disease profile and therapeutic choice. Results: Total 72 prescriptions were analyzed for the study in which 475 drugs were prescribed to the patients.  Total antidiabetic drugs prescribed to the patients were 169. Out of 72 cases 39 were males and 33 were females with mean age 66.04 ± 5.80 (Mean ± SEM). The average number of drugs per prescription was 6.59 which was very high as per guidelines. Most commonly prescribed antidiabetic drug was Metformin (63.89%) followed by Glimepiride (31.95%). Conclusion: This study reflects that there is need to make available the standard therapeutic optionat University Health Care Facility based upon pharmacoeconomic considerations.